Trigonometria e geometria : uma abordagem conjunta - Silva, Denis Apolinário da (2014)
The relationship between Geometry and Trigonometry goes beyond the classic way in which these two areas of mathematics are presented in high school. There is a tendency to separate them by rigid boundaries, restricting somehow cooperation between the methods and techniques of one of them in the other in order to solve certain mathematical problems, whose solution is not compulsorily insured in a particular area. For example, problems proposed in the Olympics. In this work we will show some possibilities of interaction, working with situations where from geometrical results we obtain certain trigonometric results and otherwise.